PENGARUH INTEGRITAS, OBYEKTIVITAS, KERAHASIAAN, DAN KOMPETENSI PADA KINERJA AUDITOR INSPEKTORAT KOTA DENPASAR - Ariani, Komang Gunayanti; Badera, I Dewa Nyoman (E-Jurnal Akuntansi, 2015)
Supervision is one of the spearheads creation of good governance. The high demand for local governance that is transparent, clean and free from corruption, collusion, and nepotism is required to make the better performance of the inspectorate. The purpose of this study was to determine the effect of integrity, objectivity, confidentiality, and competency in the performance of the auditor's Inspectorate of Denpasar. The population of this study were 45 people working in the Inspectorate auditors Denpasar. The sampling technique used is the entire population of the census method used as respondents. This study uses the technique of multiple linear regression analysis (multiple regression analysis). The analysis showed integrity, objectivity, confidentiality, and competency significant and positive impact on the performance of the auditor's Inspectorate of Denpasar.
Keywords: performance, integrity, objectivity, confidentiality, competence